The Time Moving exhibit: Exploring perceptions of time in end‐of‐life experiences. (15th January 2022) - Sellen, Kate; McGovern, Molly; MacGregor, Emma; Halleran, Laura; Ly, Lawrence
Abstract: Background: Conversations about end of life rarely take place beyond healthcare spaces and in advance of imminent death. As the Canadian ageing population increases and new policies and options emerge for end‐of‐life choices, there will be an increasing need for supports for decision‐making on end of life. Time Moving was a participatory art exhibit created to engage participants in reflections on end‐of‐life experiences and the ways in which their perception of time fluctuated within these moments. Design: A participatory and constructivist approach informed decisions on exhibit design and analysis. The Time Moving exhibit was installed in a downtown university hall for 10 days during the 2019 annual DesignTO festival, open to all members of the public. The exhibit was used as the primary method of data collection. There were three prompts informed by concepts from prior work on time perception. Participants were invited to respond by drawing, writing or constructing. Outcome: There were over 120 contributions of participants over the duration of the Time Moving exhibit. These contributions revealed new insights related to temporal perception and end‐of‐life experiences. Participants shared their perception of time during end‐of‐life experiences in a variety of ways, revealing a diversity of perceptions of time beyond calendar and clock time, including time experienced as a spiral. Conclusions: The insights on time perception highlight opportunities for approaching dialogue on end of life and in grief support, and for exhibit as a mechanism for research and education. Patient or Public Contribution: As a public exhibit, over 120 people contributed ideas, personal stories, drawings and other creative outputs to the exhibit. An estimated 250 people visited the exhibit.